Measurement report: Vertical distribution of biogenic and anthropogenic secondary organic aerosols in the urban boundary layer over Beijing during late summer - Ren, Hong; Hu, Wei; Wei, Lianfang; Yue, Siyao; Zhao, Jian; Li, Linjie; Wu, Libin; Zhao, Wanyu; Ren, Lujie; Kang, Mingjie; Xie, Qiaorong; Su, Sihui; et al. (Atmospheric chemistry and physics, 2021)
Secondary organic aerosol (SOA) plays a significant role in atmospheric chemistry. However, little is known about the vertical profiles of SOA in the urban boundary layer (UBL). This knowledge gap constrains the SOA simulation in chemical transport models. Here, the aerosol samples were synchronously collected at 8, 120, and 260 m based on a 325 m meteorological tower in Beijing from 15 August to 10 September 2015. Strict emission controls were implemented during this period for the 2015 China Victory Day parade. Here, we observed that the total concentration of biogenic SOA tracers increased with height. The fraction of SOA from isoprene oxidation increased with height, whereas the fractions of SOA from monoterpenes and sesquiterpenes decreased, and 2,3-dihydroxy-4-oxopentanoic acid (DHOPA), a tracer of anthropogenic SOA from toluene oxidation, also increased with height. The complicated vertical profiles of SOA tracers highlighted the need to characterize SOA within the UBL. The mass concentration of estimated secondary organic carbon (SOC) ranged from 341 to 673 ng C m−3. The increase in the estimated SOC fractions from isoprene and toluene with height was found to be more related to regional transport, whereas the decrease in the estimated SOC from monoterpenes and sesquiterpene with height was more subject to local emissions. Emission controls during the parade reduced SOC by 4 %–35 %, with toluene SOC decreasing more than the other SOC. This study demonstrates that vertical distributions of SOA within the UBL are complex, and the vertical profiles of SOA concentrations and sources should be considered in field and modeling studies in the future.